Diseminasi Budidaya Ikan Dalam Ember Sebagai Solusi Kegiatan Budidaya di Lahan Sempit - Ninuk Purnaningsih; Gema Aisyiyah Masruri; Thouriqul Ihsan; Budi Tryantono; Reyfan Almer (Jurnal Pusat Inovasi Masyarakat (PIM), 2021)
Fish is a useful source of food because it has protein, fat, vitamins and minerals. There are problems that occur in marine waters, namely pollution and ecosystem damage. Therefore, aquaculture experts began to seek for solutions to the community so that they could still consume fish that has high in nutrients, namely culture on land, which is known as budikdamber. Budikdamber was socialized in Ulak Karang Utara Village, which was equipped with a pre-test and post-test with an average value of 76.67 and 86.67, indicating that the socialization was running fluently. However, in practice, fish fry die up to 90% after about a week of rearing. The cause of death is ammonia attack and lack of dissolved oxygen content in water. Any other explanation would be better if tested in a laboratory. Keywords: ammonia, aquaculture, fish, dissolve oxygen